Gulma Utama Pada Tanaman Terung Di Desa Wanakarta Kecamatan Waeapo Kabupaten Buru - Muhamad Riadh Uluputty (Faculty of Agriculture, Pattimura University, 2014)
Eggplant (Salonum melongena L) is a native plant of the tropics, this plant originated from South East Asia, including Indonesia. Eggplant plants including one family with pepper, tomatoes, and potatoes. These plants belong to one group of seed plants that produce seeds and crops a year are shaped shrubs. purpose of this study is menginvertarisasi the types of weeds present in the planting eggplant in Wanakarta Village District of Waeapo. The results showed that weed found in eggplant planting area in the Wanakarta Village of Waeapo District no types namely Cyperus rotundus (L), Cyperus kyllingia, Eulisina indica (L), Drymaria cordata (L), Mimosa pudica (L) and Amaranthus spinosus. Density and dry weight Nisbih types nisbih highest species is Cyperus rotundus L is equal to 30.27% and 58.79%, while the frequency nisbih weed species is the same for all types ie 16.67%